Determinants of stock returns of property and real estate companies - Nurhaliza; Nurlaela, Siti; Nur Rois, Dimas Ilham (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
Stock returns are financial gains and losses obtained by investors due to their willingness to tolerate uncertainty and possible losses arising from their investments. Investment has the main goal of making a profit. The study aims to analyze and assess the influence of ROA, DER, EPS, and firm size on stock returns. The focus of this research is on property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. The sample amounted to 15 companies using purposive sampling. The annual report from 2019 to 2022 is the secondary data used in this study. The study utilizes multiple linear regression analysis. The results of the study stated that ROA and DER affect stock returns, while EPS and firm size did not affect stock returns